(untitled) (British Journal of Global Ecology and Sustainable Development, 2023)
The article explores the efficiency of employing the grammatical translation method for learning Russian as a foreign language. This method, recognized as the oldest approach to language acquisition, is evaluated for its effectiveness in this study through quantitative research. The assessment relies on a questionnaire to gauge students’ perspectives on how much this method aids in their acquisition of the Russian language.